Aspectos morfológicos e morfométricos da cicatrização da anastomose colônica, em ratos, sob ação de enema de aroeira-do-sertão a 10% (Myracrodruon urundeuva Fr. All.) - Goes, Annya Costa Araújo de Macêdo (2004)
The surgical procedures for treatment of colonic diseases are common in medical practice. Colonic anastomoses dehiscences can determine considerable morbidity and mortality. The healing of these anastomoses is a complex process, and several factors can modify its evolution. Anti-inflammatories have interested researchers, for the potential to interfere on the phases of inflammation and fibroplasia of the healing process. The aroeira-do-sertão (Myracrodruon urundeuva Fr. All.) is a plant popularly used as an anti-inflammatory and promoter of healing, in several affections. In this study, the purpose was to evaluate the action of the 10% aqueous extract of aroeirado- sertão, under the form of enemas, on colonic anastomosis, in rats. There were utilized 48 Wistar rats, males, with average weight 320 g, distributed in two groups, with 24 animals, each. All animals were subjected to laparotomy, with complete transverse section of the descending colon, followed by colonic anastomosis. The rats on group A received daily, post-operative, enemas of carboxymethylcellulose (CMC) based vehicle, until the date of euthanasia. The animals on group B received daily, post-operative, enemas of 10% aqueous extract of aroeira-do-sertão in CMC based vehicle. On dates 3, 7, 14 and 21 of the experiment, six rats in each group were subjected to removal of a colonic segment, including the colonic anastomosis, destined to histological appreciation and qualitative and quantitative analysis of inflammatory and healing cell response. The morphological evolution of the healing process was significantly lower on the group aroeira than on the group control, on day 7 of the experiment (ρ < 0,05). On the morphometric evaluation, it was verified less neutrophilic migration, on days 7 and 21, and more angiogenesis and fibrogenesis, on day 14, on the group aroeira (ρ < 0,05). There was also less deposition of collagen, on days 3, 7 and 14 of the experiment, on the group aroeira (ρ < 0,05). It is concluded, therefore, that aroeira is efficient as an anti-inflammatory, because it diminishes the intensity of the initial (day 7) acute inflammatory response, during the healing of colonic anastomoses. However, in spite of showing angiogenic and fibrogenic action (day 14), there is delay on collagen deposition (days 3, 7 and 14), on the group aroeira. Later on (day 21), however, aroeira does not cause histological alterations on the healing process.